PENGEMBANGAN DIMENSI KUALITAS LAYANAN E-BANKING DAN HUBUNGANNYA DENGAN KEPUASAN SERTA LOYALITAS KONSUMEN - Tan, Alfian; Sukapto, Paulus; Sitompul, Carles (Jurnal Ilmiah Teknik Industri, 2014)
SERVQUAL is a service quality measurement model that is assumed to be widely applicable in every sector of service industry, yet research proves the opposite. Characteristic of customer in each segment can be a factor that causes differences in measurement model. According to that fact, this research is conducted to identify the difference of measurement model in each customer segment, especially in e-banking industry. Not only we identify the measurement model,  this research is done to confirm the relationship between 3 constructs as well, which are service quality, satisfaction, and loyalty. Several statistical method will be introduced here in relationship with segmentation process, measurement model identification, dan the three constructs' validation process. Segmentation process yields 2 customer segments which are people with high and moderate expectation to service quality. In the first segment, the measurement model consists of 4 quality dimensions, which are fullfilment, efficiency, assurance, and web design while there are 5 dimensions in the second segment which are fulfillment, responsiveness, information technology, assurance, and efficiency. There are also significant relationships among service quality, satisfaction, and loyalty.